2009
DOI: 10.2165/11318860-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib

Abstract: Sunitinib is an oral oxindole multitargeted kinase inhibitor that inhibits certain receptor tyrosine kinases (RTKs). These include vascular endothelial growth factor receptors (VEGFR type 1 and 2), platelet-derived growth factor receptors (PDGFR-alpha and PDGFR-beta), stem cell factor receptor (KIT), FMS-like tyrosine kinase-3 (FLT3), glial cell-line derived neurotrophic factor receptor (RET) and the receptor of macrophage-colony stimulating factor (CSF1R). Examination of the antitumor effect of sunitinib in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(67 citation statements)
references
References 94 publications
0
67
0
Order By: Relevance
“…Zhu et al [22] found a baseline K trans distribution for HCC between 1.25 and 2.50 min −1 and k ep ranging between 1.5 and 3.0 min −1 using DCE-MRI for 34 patients enrolled in a phase II study of multitargeted kinase inhibitor sunitinib [62]. Hsu et al [23] reported baseline K trans between 0.4 and 4.5 min −1 in 31 patients with advanced HCC treated with sorafenib plus tegafur/uracil that underwent a DCE-MRI examination.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [22] found a baseline K trans distribution for HCC between 1.25 and 2.50 min −1 and k ep ranging between 1.5 and 3.0 min −1 using DCE-MRI for 34 patients enrolled in a phase II study of multitargeted kinase inhibitor sunitinib [62]. Hsu et al [23] reported baseline K trans between 0.4 and 4.5 min −1 in 31 patients with advanced HCC treated with sorafenib plus tegafur/uracil that underwent a DCE-MRI examination.…”
Section: Discussionmentioning
confidence: 99%
“…Sunitinib is a small molecule, able to inhibit a multiplicity of TK receptors including the platelet-derived growth factors PDGFRα/β, the colony stimulating factor type I (CSF-1R), the vascular endothelium growth factor (VEGFR), the stem cell factor c-KIT, and the fetal liver TK receptor 3 (FLT3) amongst others (Faivre et al, 2006; Papaetis and Syrigos, 2009). Owing to this ability to inhibit diverse multiple TK receptors, sunitinib has shown capacity to arrest angiogenesis, metastasis and tumor progression (van Erp et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we wanted to investigate the effects of agents that have been shown to interfere with the activity of such receptor pathways. Sorafenib and sunitinib have been shown to inhibit the activity of a number of cytokine receptors, including vascular endothelial growth factor receptor (VEGFR), platelet-derived growth factor receptor (PDGFR), stem cell factor receptor (c-Kit) and FMS-like tyrosine kinase-3 (Flt-3) [13,14]. In the next set of experiments, the three AT/RT cell lines were evaluated for sensitivity to sorafenib and sunitinib by in vitro cytotoxicity assays.…”
Section: Resultsmentioning
confidence: 99%